Influecing Factors Reccurence of Adult Asthma - Novita Sri Rahayu; Widaryati Widaryati (Media Keperawatan Indonesia, 2023)
Asthma is not contagious but this disease includes high morbidity and mortality in severe cases. Asthma can relapse with severe asthma exacerbations associated with loss of asthma control. So it is important to know the influencing factors in order to control the recurrence. The purpose of this study is to find out what factors affect recurrence in adult asthma sufferers, through researching literature on the phenomenon of adult asthma recurrence. The research method using literature search is carried out through google scholar and PubMed. The keywords used in adult asthma and recurrence factor. The search was carried out from 2017-2022, and 4 journals were reviewed which had been selected using PRISMA diagrams and were tested for feasibility using JBI critical appraisal. The results of 4 journals that have been analyzed show that the factors that affect recurrence in adult asthma patients are influenced by dust, airway infestation, weather changes, cigarette smoke, exercise, stress, anxiety and pregnancy. It is hoped that the results of this study for patients can be used as supporting information in controlling recurrences, and for nurses, it can be used as a reference for health education in asthma sufferers to prevent asthma recurrences.